Factors Contributing for Sustainability of SHGs Members in Karnataka – A Case Study of Tumkur District - Dr. M. Subramanyam, Dr. K. Sreenivasa Murthy, Dr. Harani B. (International Journal of Advanced Science and Technology, 2020)
The present paper deals with the prospectus and sustainability of self-group members in the study area of urban and rural. The study is mainly based on primary data, collected from 500 SHG members located in different places in Tumkur district. This ensured to get the number of sample size determined with the help of statistical tool. The overall object of the present micro level study is to analyse a comparative study on sustainability of self-help group members in urban and rural area in Tumkur District. The feature of the group like status , tenure of membership, training, sources of knowledge ,experience in the group , meetings , attendance, the reasons to join SHGs and overall impact of enterprises on quality of life of members of self-help groups members after joining SHG in urban and rural area. SHGs in Tumkur District play a predominant role in mobilizing and managing thrift activities, appraising the credit needs, enforcing financial disciplines, maintaining credit linkages with banks and effectively undertaking income generating activities which influence the poverty alleviation